Energy, exergy, exergoeconomics, and exergoenvironmental assessment of three brine recycle humidification-dehumidification desalination systems applicable for industrial wastewater treatment. (1st February 2020) - Ghofrani, Iraj; Moosavi, Ali
Graphical abstract: Highlights: A new brine recycle humidification-dehumidification system is introduced. Three different systems are studied in high salinity feed and recovery ratios. A complete assessment was carried out on the systems. The effects of the parameters are determined on the performance of the systems. Selecting the best system highly depends on the steam and electricity prices. Abstract: Using zero liquid discharge systems is one of the efficient methods to reduce the negative environmental impact of the brines of the desalination systems and also to recycle the industrial wastewaters for reuse. Due to the simple fabrication process, low maintenance cost, intensive to inlet water quality, and the ability to use renewable and low-grade-heat, modified humidification-dehumidification systems may be a proper choice for the zero liquid discharge applications. Thus, in the present study, the energy, exergy, exergoeconomic, and exergoenvironmental assessment of three advanced brine recycle humidification-dehumidification systems for zero liquid discharge operation are comprehensively investigated. The first system is heat-driven: (1) brine recycle humidification-dehumidification system which is driven by heat and the two other systems are electricity-driven: (2) brine recycle humidification-dehumidification desalination system coupled with a heat pump in which the evaporator is as the dehumidifier, (3) brine recycle humidification-dehumidification desalination system coupled with a heat pump in which the evaporator is after the humidifier. The last system is a new proposed system in this study. The configuration of the humidification-dehumidification systems is closed-water closed-air. Operating parameters of the systems are independent of the recovery ratio of the systems. In the three considered systems, the exergoeconomic and exergoenvironmental factors are almost very low; thus, improving thermodynamic efficiencies of the components is necessary for fresh water cost and environmental impact reduction, and there is room for improvement to reduce exergy destruction without any more investment expenses. Based on the relative cost difference and the relative environmental impact difference in the systems, the dehumidifier and the evaporator are the components with the highest improvement potentials. In terms of the produced fresh water cost brine recycle humidification-dehumidification desalination system coupled with a heat pump in which the evaporator is after the humidifier system is superior to the two other systems (When heating steam price higher than 5 $/GJ); also the environmental impact of the produced fresh water in brine recycle humidification-dehumidification desalination system coupled with a heat pump in which the evaporator is after the humidifier system is lower than the two other systems. In electricity-driven systems, the water cost can be reduced by using R600 and R245fa instead of R134a.